The relationship between technical efficiency, firm growth and market structure in the Indonesian palm oil industry - Berliana Anggun Septiani; Maman Setiawan (Cogent Economics & Finance, 2023)
This research investigates the relationship between efficiency and firm growth as well as the relationship between firm growth and market structure (CR4) to evaluate whether the quiet-life (QL) and/or efficient structure (ES) hypothesis applies in the Indonesian palm oil industry. This study uses large and medium industry survey data sourced from the Indonesian Bureau of Central Statistics (BPS) for the period from 1990 to 2017. The efficiency score is calculated using data envelopment analysis (DEA) using a bootstrapping approach. The two-step generalized method of moments (GMM) and panel vector auto regression (PVAR) are used to test the two hypotheses. The results show that technical efficiency can increase a firm's market share, market concentration, and market power. These results support the ES hypothesis. This research also finds that market structure (CR4) has an impact on firm efficiency, providing evidence supporting the QL hypothesis. These results indicate that the ES and QL hypotheses apply in Indonesia during a business cycle that needs to be considered by policymakers.
Keywords: 330; industry concentration; palm oil industry; technical efficiency; the efficient structure hypothesis; the quiet-life hypothesis